"Beach Lifeguards' Sun Exposure and Sun Protection in Spain" - Magdalena de Troya Martín; Nuria Blázquez Sánchez; Cristina García Harana; Mª Carmen Alarcón Leiva; José Aguilera Arjona; Francisco Rivas Ruiz; Mª Victoria de Gálvez Aranda (Elsevier, 2021)
Background: Sunburn is the main avoidable cause of skin cancer. Beach lifeguards spend many hours exposed to the effects of solar radiation during their work day, precisely at times of the year when levels of solar irradiation are highest. The aim of this study is to quantify the risk to beach lifeguards of sun exposure. Methods: A descriptive cross-sectional study was carried out in the Western Costa del Sol, southern Spain, during the summer of 2018. The research subjects were recruited during a skin cancer prevention course for beach lifeguards. All participants were invited to complete a questionnaire on their habits, attitudes, and knowledge related to sun exposure. In addition, ten were specially monitored using personal dosimeters for three consecutive days, and the results were recorded in a photoprotection diary. A descriptive analysis (mean and standard deviation for the quantitative variables) was performed, and inter-group differences were evaluated using the Mann-Whitney U test. Results: Two hundred fifteen lifeguards completed the questionnaire, and 109 met the criteria for inclusion in this analysis. The mean age was 23.8 years (SD: 5.1), 78.0% were male, 71.5% were phototype III or IV (Fitzpatrick's phototype), and 77.1% had experienced at least one painful sunburn during the previous summer. The mean daily personal ultraviolet exposure per day, the minimal erythema dose, and the standard erythema dose, in J/m2, were 634.7 [standard deviation (SD): 356.2], 2.5 (SD: 1.4) and 6.35 (SD: 3.6), respectively. Conclusion: Beach lifeguards receive very high doses of solar radiation during the work day and experience correspondingly high rates of sunburn. Intervention strategies to modify their sun exposure behavior and working environment are necessary to reduce the risk of skin cancer for these workers and to promote early diagnosis of the disease.